STAGES OF PHYSICAL EXERCISE PRESCRIPTION AS A METHOD FOR THE PREVENTION AND TREATMENT OF TYPE 2 DIABETES: A PROPOSAL FOR INTERVENTION AND CONTROL - Mendoza Hinestroza, Mercedes; Rodríguez Sarmiento, David Leonardo; Prada Rozo, Mauricio Javier; Sarmiento Herrera, Carlos Eduardo; Murcia Izquierdo, Néstor Javier (Documentos de trabajo ECISA, 2025)
This article refers to a proposal for the prevention and control of type 2 diabetes. In this sense, this proposal includes the following stages: Stage Ia: Individuals with risk factors for developing type 2 diabetes. Stage IIb: People with prediabetes who present with insulin resistance. Stage IIIc: Individuals with type 2 diabetes mellitus, whether or not medicated with metformin, who present with insulin resistance and mitochondrial dysfunction as a metabolic component of the disease. Stage IVd: Individuals with complications derived from the disease and cardiovascular risk factors. These stages would be related to the direct variables of VO2 max index (mitochondrial dysfunction), cognitive and mental health status (depression, anxiety, motivation levels, stress), and indirect variables of fatigue indices, quality of life index, and their influence on adherence to physical exercise. In this study, a bibliographic review was conducted in specialized databases. This literature review has led the authors to propose a method for categorizing the Stages of Physical Exercise Prescription (EPEF) based on the literature reviewed. This method seeks to unify the criteria for effective exercise prescription, serving as a basis for risk factor intervention and the control of type 2 diabetes. These criteria are useful as a measure to optimize intervention outcomes at the different stages of exercise prescription proposed in this proposal.